System of management of the process of the quality of service in the attention and level of satisfaction of the producer in the fund for the socialist agrarian development lara state. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
Overview assess the management of the process of the service quality in the attention and level of satisfaction of the producer in the bottom for the period 2014-2015, was achieved with a design of descriptive, analytic method of three-phase. A survey called CESASI to 59 public servants and a survey aimed at 56 producers of the Andrés Eloy Blanco municipality is applied. It was determined that the institution has an organization chart, mission and vision detecting faults in the mentioned areas where have technological programs that usually are not operating. The Fund does not comply with ISO 9000 and 9004 standards, doesn't care about improving the human talent, does not comply with the realization of the product and/or service since there is no responsibility on the measurement of quality of the service, creating a level of dissatisfaction of the internal and external clients on administrative activities since the financing are delivered at the wrong time.
Keywords: process management system; assurance of quality; customer satisfaction